The name of the rose: Analysis of philosophical clashes - Silva, Cristiano Dias da (Seven Editora, 2023)
This article discusses how philosophy is represented in the work O Nome da Rosa by Umberto Eco. Therefore, it analyzes the literary text by finding the medieval philosophies that are in the speeches of the characters, explaining how such philosophies are related to theories outside the medieval environment. . The text of the beginning of the work related to the arrival at the abbey and the episode of the horse Brunello were researched, through a critical study of the comparative literature. The analysis of the text showed references to Charles Peirce’s semiotics; the nominalism of Guilherme Ockham; and Buridano regarding the theory of the world encyclopedia. It also made it possible to find the analogy of the world as a book or mirror, referring to Alan das Ilhas; the connections with Roger Bacon’s new science, the clashes between realism and nominalism, finally, the reference to the Aristotelian theory of causality. The result shows that the literary text appears as a tool for the study of philosophy: first as a text that reveals other philosophical texts; second as a didactic instrument that, through verisimilitude, makes the world of philosophy more accessible. DOI:https://doi.org/10.56238/chaandieducasc-026